Emerging roles of pyruvate dehydrogenase phosphatase 1: a key player in metabolic health - Kumar, Vikalp; Greenberg, Miriam L. (Frontiers in Physiology, 2025)
Pyruvate dehydrogenase phosphatase (PDP), a structurally conserved member of the protein phosphatase C family (PP2C) of proteins, is a key regulatory enzyme responsible for reactivation of the mitochondrial gate-keeper, pyruvate dehydrogenase (PDH). Tissue-specific expression of PDP isozymes, specifically PDP1 and PDP2 facilitate regulation of the multi-subunit PDH, influencing flux of substrates to the TCA cycle. PDP1 is a heterodimeric, Ca2+ sensitive isoform, predominantly expressed in muscle tissue where its role in regulating PDH activity is well established. Emerging research suggests that it is involved in various diseases, including pancreatic ductal adenocarcinoma, cardiomyogenesis defects, traumatic brain injury, and Barth syndrome. In this review, we discuss recent studies revealing the crucial role of PDP1 and its dysregulation in various metabolic disorders, thereby highlighting its potential as a therapeutic target for these debilitating diseases.